Relationship between submaximal oxygen consumption and bone mineral density differs between triathletes and marathoners - Outwin, J. R.; Davis, F.; Melvin, A. C.; Stump, O.; Reed, S.; Kozloff, K. M.; Lepley, A. S. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Maintaining bone mineral density (BMD) is a crucial component of lifelong bone health and is particularly important for injury prevention in sport. Athletes participating in high impact sports have higher BMD compared to running athletes [1], underscoring the importance of mechanical loading in osteogenesis [2]. In contrast, cyclists and swimmers are at a greater risk for osteopenia due to low mechanical loading [3]. Currently, there is a dearth of information about BMD in triathletes, combining running, cycling and swimming. Given that aerobic fitness may influence the extent to which an athlete can generate osteogenic bone stress during training, the purpose of this study was to assess the relationship between submaximal and maximal oxygen uptake and BMD across endurance athletes involved in multiple activities vs. endurance running alone.